The Paradox of Participation: Social Diversity and Governance Accountability in Thasang Rural Municipality, Mustang, Nepal - Manita Hamal; Mohan Kumar Paudel; Ramchandra Baral; Saroj Raj Pant; Suveksha Panta (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This paper examines the efficacy of governance in Thasang Rural Municipality, a Kaligandaki river belt locality within the lower Mustang of Nepal. The prime issue that is examined relates to how caste and other identities shape participation in terms of accountability and social diversity. Primary data were collected from a total sample of 151 respondents, Thakali ethnic groups in the study area, in 5 different wards which seems a reasonable sample size. The findings show a limited and unequal participation of people within different groups, more specifically for the marginalized groups Dalits and Magars. The public hearings are set up officially but are not performed and very few are attended while most of the respondents have said to attend the public hearings sometimes. The manifest role of local authority regarding service delivery seems to be significant variation in ward-specific results indicating inconsistency in efficacy of governance. This implies a growing gap between Defacto and Dejure participation of citizens which calls into question inclusivity and accountability in local settings. In general, it calls for significant institutional reform and effort toward addressing social inequalities with real public participation to be ensured and services to be improved. It provides a basis for further study and has practical relevance to local governments' future planning and intervention.